Introduction: everyday multiculturalism in/across Asia. Issue 5 (8th April 2020) - Walton, Jessica; Harris, Anita; Iwabuchi, Koichi
ABSTRACT: This article introduces the special issue, Everyday Multiculturalism in/across Asia. It provides an overview of the international and inter-disciplinary research papers included in the special issue which all speak to the concept of everyday multiculturalism by critically engaging with the extent to which core aspects relate to different contexts in and across Asia. Papers in this collection encompass research undertaken in Australia, Hong Kong, Malaysia, Singapore and South Korea and which include issues of intraregional movement and labour mobility particularly regarding the experiences of migrants from Burma, China, Nepal, The Philippines and India. A key contribution of this special issue is that the papers engage with empirical, theoretical and methodological questions which consider the potential transferability of ideas related to everyday multiculturalism, especially in the context of expanding trans-Asian mobilities.